TALABALARDA XULQ OG᾽ISHINI DIAGNOSTIKA QILISH VA KORREKTSIYALASHNING PEDAGOGIK-PSIXOLOGIK XUSUSIYATLARI - Turumbetova, Z. (SCIENCE and SOCIETY, 2024)
The article describes deviant human behavior - moral qualities that do not correspond to generally accepted or officially established social norms and its manifestation in various forms.
Keywords: ethics; deviant behavior; abnormal; prevention; intervention